SPIRIT DARI RUMAH GAYA JENGKI ULASAN TENTANG BENTUK ESTETIKA DAN MAKNA - Widayat, Rahmanu (Institute of Research and Community Outreach - Petra Christian University, 2006)
This paper began from writer's concern regarding the decrease in Jengki style houses and threatened to be lost from our sight. Whereas, this Indonesian house or architectural style had coloured the big cities and even the small cities back in the sixties till the seventies. This had triggered the writer to attempt to present the Jengki house style regarding its form, aesthetics, and its meaning. Based on several concept approaches such as form follows function, eclectic concept, and art (architecture) as an expressive symbol, it is hoped that Jengki style houses could be revived in its former position of dominance in Indonesian architecture, in other words, not forgotten just like that. But more than that, it could promote the spirit in giving rebirth to unique Indonesian styles in houses and architecture. Abstract in Bahasa Indonesia : Tulisan ini berawal dari keprihatinan penulis karena semakin berkurangnya rumah gaya jengki, dan terancam lenyap dari pandangan. Padahal rumah gaya Jengki pada tahun 60-an sampai dengan 70-an pernah mewarnai tampilan kota-kota besar bahkan kota-kota kecil di Indonesia. Untuk itu penulis mencoba mengetengahkan rumah gaya jengki dilihat dari sisi bentuk, estetika, dan maknanya. Menggunakan pendekatan beberapa konsep seperti form follows function, konsep eklektik, dan seni (arsitektur) sebagai ekspresi simbol, dengan harapan dapat mendudukkan rumah gaya jengki pada tempat sewajarnya dalam ranah arsitektur Indonesia. Artinya tidak dilupakan begitu saja. Namun lebih dari itu, dapat diambil spiritnya dalam konteks melahirkan gaya rumah atau arsitektur yang khas Indonesia. Kata kunci: rumah gaya jengki, bentuk, estetika, makna